Phononic and magnetic excitations in the quasi-one-dimensional Heisenberg antiferromagnet KCuF3 - Gnezdilov, V.; Deisenhofer, J.; Lemmens, P.; Wulferding, D.; Afanasiev, O.; Ghigna, P.; Loidl, A.; Yeremenko, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The Raman-active phonons and magnetic excitations in the orbitally ordered, quasi-one-dimensional Heisenberg antiferromagnet KCuF3 are studied as a function of temperature in the range between 3 and 290 K in various scattering configurations. The low-energy Eg and B1g phonon modes show an anomalous softening ( 25% and 13%) between room temperature and the characteristic temperature TS = 50 K. In this temperature range a freezing-in of F– ion dynamic displacements is proposed to occur. In addition, the Eg mode at about 260 cm–1 clearly splits below TS. The widths of the phonon lines above TS follow an activated behavior with an activation energy of about 50 K. Our observations clearly evidence a reduction of the lattice symmetry below TS and indicate a strong coupling of lattice, spin, and orbital fluctuations for T > TS. A strongly polarization dependent quasielastic scattering is observed at temperatures above TN = 39 K due to magnetic-energy fluctuations. For temperatures below TN a rich spectrum of additional modes is observed, with different lineshape, polarization and temperatures dependence. We attribute them to longitudinal and transverse magnetic modes as well as to a continuum of magnetic excitations.